The relationship between stillbirth, SGA and placental histopathology. (18th April 2012) - Muid, T; Sharp, A; Roberts, D
Abstract : There is increasing evidence that small for gestational age (SGA) fetuses and abnormal placentation have an important role in stillbirth. We wanted to explore what proportion of unexplained stillbirths in our population had abnormal placentation which could potentially be screened for in the antenatal period. To determine the proportion of unexplained stillbirths with abnormal placental histopathology. Retrospective review of all stillbirths (n=333) at Liverpool Women's NHS Foundation Trust between 2005 and 2010. Placental histopathology was reviewed for 139 stillbirths unexplained by maternal or fetal conditions. Strict histopathological criteria were used to demonstrate maternal vascular underperfusion (MVUP) or fetal vascular occlusion (FVO). 59%, (n=81) of unexplained stillbirths were SGA (<10th centile on customised charts). Half of these (52%; n=42) demonstrated MVUP. Only 4% (n=6) of normal birthweight stillbirths demonstrated MVUP. SGA stillbirths accounted for 87.5% (n=42) of all unexplained stillbirths with MVUP. There was evidence of FVO in a small number of unexplained stillbirths (6%; n=9), and an even smaller proportion of SGA stillbirths (4%; n=4). Our data suggests that MVUP is an important contributory factor to SGA associated stillbirth, but not for stillbirths with normal birth weight. We hypothesise that antenatal methods for assessment of fetal growth and placental structure/function have the potential to identify up to a third of pregnancies at risk of unexplained stillbirth. Nationally, there has been little impact on the potentially preventable stillbirth. Is it time to focus on a standardised assessment in the third trimester to identify fetuses at risk of preventable stillbirth?